THERMAL COMPOSITE COATINGS IMPROVING QUALITY OF TECHNICAL MEANS OF TRANSPORT - Andrzej POSMYK; Aleksandra BOGDAN-WŁODEK (Scientific Journal of Silesian University of Technology. Series Transport)
The paper presents the thermal properties of composite insulating material designed for producing of technical means of transport. This material can be coated on most of engineering materials. The matrix of this material is an acrylic resin ant non porous ceramic microspheres made of alumina are the reinforcing phase. Thanks to that into the spheres almost vacuum (0,13 Pa) dominants and a big amount of spheres pro thickness unit is it possible to achieve low thermal conductivity. Usage of these coatings for producing of cooling cabins on vehicles let us to reduce of fuel for maintain of given temperature. Usage of these coatings in planes flying on high altitudes (temperature up to -60) allows to reduce of fuel consumption for heating. It has an important influence on transport quality and quality costs.